LOSS ANALYSIS OF ROAD CONSTRUCTION PROJECTS IN DKI JAKARTA DUE TO WASTE MATERIALS - Simbolon, Joas BM Tua; Waty, Mega (Jurnal Infrastruktur, 2024)
As an area develops, developments in all areas of construction become increasingly widespread, including the construction/improvement of road construction. In the implementation of construction projects, problems often occur, one of which is that there is still a lot of remaining material that is wasted and will cause waste (Lestari, 2022). This research aims to identify and categorize the types of materials that cause waste in road construction, as well as evaluate the percentage, causes and impact of waste on project losses. Quantitative methods are used to obtain the percentage of waste on projects using data on material type, installation volume, purchase volume and total material costs. Then the data is processed using multiple regression analysis which will be simulated in SPSS. The analysis results indicate that the types of materials most frequently contributing to waste in rigid pavement road construction/improvement projects are as follows: X1 ready-mix concrete 10.99%, X2 wiremesh iron 6.73%, X3 dowel iron 11.81%, and X4 plastic 5.11%. The sources causing the generation of waste materials include design, implementation, material procurement/handling, and residuals. Assessing the impact of waste materials on losses in road construction projects using SPSS multiple linear regression, the project loss variable is derived as Y = -711.522 + 0.749 X1 + 60.096 X3. This implies that the materials significantly affecting project losses are X1 ready-mix concrete and X3 dowel iron. The magnitude of the influence of independent variables (ready-mix concrete and dowel iron) on project losses is 58.80%. The results of this research have implications in preventing losses from road construction projects in DKI Jakarta.